Dry Needling and Antithrombotic Drugs - María Muñoz; Jan Dommerholt; Sara Pérez-Palomares; Pablo Herrero; Sandra Calvo (Pain Research and Management)
Many clinicians increasingly use dry needling in clinical practice. However, whether patients’ intake of antithrombotic drugs should be considered as a contraindication for dry needling has not been investigated to date. As far as we know, there are no publications in analyzing the intake of antiplatelet or anticoagulant agents in the context of dry needling techniques. A thorough analysis of existing medications and how they may impact various needling approaches may contribute to improved evidence-informed clinical practice. The primary purpose of this paper is to review the current knowledge of antithrombotic therapy in the context of dry needling. In addition, reviewing guidelines of other needling approaches, such as electromyography, acupuncture, botulinum toxin infiltration, and neck ultrasound-guided fine-needle aspiration biopsy, may provide specific insights relevant for dry needling. Based on published data, taking antithrombotic medication should not be considered an absolute contraindication for dry needling techniques. As long as specific dry needling and individual risks are properly considered, it does not change the risk and safety profile of dry needling. Under specific circumstances, the use of ultrasound guidance is recommended when available.